Нанодисперсные пленки, осажденные импульсным лазерным распылением комбинированных мишеней Ni-Au - Багмут, А.Г.; Багмут, И.А.; Жучков, В.А.; Николайчук, Г.П.; Красников, А.Н. (Физическая инженерия поверхности, 2010)
Представлены результаты электронно-микроскопических и электронографических исследований пленок Ni, Au и сплава Ni-Au, полученных импульсным лазерным распылением
одноэлементных и двухэлементных металлических мишеней. В результате распыления
одноэлементной мишени Ni и комбинированной мишени 0,75Ni-0,25Au на подложках формируются пленки с метастабильной ГПУ структурой. Распыление комбинированной мишени
0,5Ni-0,5Au, также как и мишени из чистого золота, приводит к формированию пленок со
стабильной ГЦК структурой. Наведені результати електронно-мікроскопічних та електронографічних досліджень плівок
Ni, Au та сплавів Ni-Au, одержаних імпульсним лазерним розпилюванням одноелементних і
двоелементних металевих мішеней. В результаті розпилювання одноелементної мішені Ni та
комбінованої мішені 0,75Ni-0,25Au на підкладках формуються плівки з метастабільною ГЩП
структурою. Розпилювання комбінованої мішені 0,5Ni-0,5Au, такожяк і мішеніз чистого золота,
призводить до формування плівок зі стабільною ГЦК структурою. The results of electron microscopic and electron diffraction investigation of Ni, Au and Ni-Au alloy
films, which was prepared by pulse laser sputtering of the single-element and of the two-element
metal targets, are presented. As a result of sputtering of single-element target of Ni and of the combined
target of 0.75Ni-0.25Au on the substrates was formed films with metastable HCP structure. Sputtering
of the combined targets of 0.5Ni-0.5Au, as well as a sputtering of targets of pure gold, results in
formation of films with stable FCC structure.
Kewords: еlectron microscopy, films of Ni-Au alloy, pulse laser sputtering, two-element target,
metastable structure, electron-diffraction, phase transition, annealing, substrate, grain size, distribution.